Impact Of Chronic Exposure Of Organophosphorus Pesticide On Hematological And Biochemical Parameters Of Agriculture Workers: A Cross Sectional Study (Journal of Pharmaceutical Negative Results, 2023)
Background:The uncontrolled long-term exposure to organophosphorus pesticides is harmful to health especially in agricultural workers. Objective:This study was designed to assess hematological and biochemical parameters of agricultural workers occupationally exposed to organophosphorus pesticides.Methodology:A cross sectional study was conducted at Baqai Medical University, Muhammadi blood bank & diagnostic center, Karachi. Samples were collected from 193 pesticide sprayers (aged 20-59 years) working for ≥ 2 years in agriculture farms, located in district Mirpurkhas, Sindh, Pakistan. A comparison was made by equal numbers of controls living in same vicinity but not involved in spraying pesticide. Complete blood count was determined on Sysmex Xp 100 automated hematology analyzer by Tokyo, Japan. Serum cholinesterase (ChE), as a biomarker of chronic organophosphorus pesticide exposure, was measured on Cobas c 311 clinical chemistry analyzer by Roche Diagnostics International Ltd and Liver function tests were performed on Cobas c111 chemistry analyzer, Germany.Results:Serum ChE level of exposed group was significantly lower than non-exposed (p <.001). 49.7% individuals in exposed group had serum ChE levels below the reference value. The hematological parameters especially Hb, RBC, MCV, MCH, MCHC, WBC, neutrophils, lymphocyte, and platelet counts were significantly altered in exposed group than non-exposed group. Hemoglobin concentration was significantly reduced in exposed group as compared to non-exposed group (p <0.001). There was significant relationship between exposure of pesticide and degree of anemia; exposed group was more likely to develop anemia than non-exposed group (p <0.001). In biochemical parameters serum alkaline phosphatase (ALP) and serum aspartate aminotransferase (AST) of exposed group was significantly high as compared to non-exposed group (p <0.001).Conclusion:Long-term exposure to cholinesterase-inhibiting agricultural pesticides is associated with alterations in hematological parameters along with deranged liver function tests.